TARANNUM PEDAGOGY: A CHRONOLOGICAL REVIEW FROM CLASSICAL TRADITIONS TO DIGITAL INNOVATION - Ramli, Mohd Shahidan; Sahad, Mohd Nizam; Mohd Din, Khairil Fikri; Abu, Ahmad Tamizi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2026)
This study presents a chronological literature review of Tarannum pedagogy, a specialized field within Qur’anic education that integrates melodic recitation, spiritual refinement, and instructional practice. Although Tarannum has long functioned as an important component of Islamic learning, existing studies remain dispersed across different themes and periods, making it difficult to trace the developmental trajectory of the field in a systematic manner. Accordingly, this review aims to examine the evolution of Tarannum pedagogy over time by identifying major patterns, shifts in research orientation, and emerging instructional trends in the literature. The study employed a systematic advanced search strategy using the Scopus database, guided by the main keywords tarannum, pedagogy, and recitation. Relevant records were screened according to predefined criteria to ensure thematic relevance and academic quality. A final dataset of 77 primary studies (n = 77) was selected for analysis. The findings reveal a clear upward trend in research productivity and conceptual development across three chronological phases: Foundational and Sparse Emergence (2002–2013), marked by limited and exploratory studies centered on traditional recitational practices; Transitional Growth and Pedagogical Structuring (2014–2018), characterized by increasing scholarly attention to structured teaching methods, curriculum concerns, and early digital interventions; and Rapid Expansion and Digital Integration (2019–2025), distinguished by strong publication growth, wider empirical inquiry, and the incorporation of multimedia, speech technologies, online learning platforms, and artificial intelligence into Tarannum-related instruction. Numerically, publication activity rose from isolated outputs of 1–2 studies per year in the earliest phase to 5–8 studies annually in the transitional and early expansion years, before reaching a peak of 11 publications in 2023, with sustained high output in 2024 and 2025. Overall, the review demonstrates that Tarannum pedagogy has evolved from a tradition-based instructional practice into a more structured, research oriented and technology responsive domain, offering a valuable foundation for future pedagogical innovation and interdisciplinary scholarship in Qur’anic education.